(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Marine Jurassic sediments (Bajocian-Tithonian) of the Kachchh Basin were deposited in a ramp setting. Except during the Middle and Late Bathonian, when a carbonate regime became established, the fill of the basin consists predominantly of siliciclastics. The sediments represent environments that range from coastal plains (rivers and associated flood plains with caliche nodules), deltas, brackish water lagoons, nearshore sand and iron-oolite bars of the inner ramp, generally situated above fair-weather wave-base, to the middle ramp influenced by storm-waves and by storm-generated currents, and finally to the outer ramp which is characterised by low energy, fine-grained sediments. Changes in relative sea level produced a cyclic sedimentation pattern. The rich benthic fauna of macroinvertebrates is dominated by bivalves, followed by brachiopods, gastropods, corals, serpulids, and sponges. The analysis of 370 statistical samples and more than 27, 000 specimens produced more than 40 benthic associations and assemblages. They show a relationship to several environmental parameters, two of which, salinity and climate, are briefly discussed. The spatial distribution of the facies and biota is outlined for two time slices, the Bathonian and the Callovian-Oxfordian, respectively.